Epilogue. Issue 3 (2nd September 2019) - Reinelt, Janelle
ABSTRACT: The author reviews her understanding of the term 'worksite of democracy', its origins in Etienne Balibar's work, and its application to the present context of performance. She sums up the efforts of the special issue and points the way to future deployment of the concept for performance studies.